Conductive agent and preparation method thereof, negative pole piece and lithium ion battery
By using gasified ash slag to prepare conductive agent materials, the problem of high cost of existing conductive agent materials is solved, and the effects of low cost, strong conductivity and good compatibility are achieved, and there is good industrial application prospect.
Patent Information
- Application Number
- CN202311160389.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-11
AI Technical Summary
The existing lithium-ion battery conductive agent materials are costly and difficult to meet the actual application needs.
The gasified ash slag is used as raw material to prepare conductive agent materials by ball milling, surface acid removal and calcining treatment. This method is not only low in cost, but also has low usage, and has good industrial application prospects.
The prepared conductive agent material has low cost, high carbon content, strong conductivity, large specific surface area and good compatibility. It can be used as a good conductive agent material and combined with a variety of existing negative electrode active materials.
Smart Images

Figure CN119601662A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of lithium-ion batteries, and in particular to a conductive agent and a preparation method thereof, a negative electrode sheet and a lithium-ion battery. Background Art
[0002] The weight percentage of the conductive material in the negative electrode of lithium-ion batteries generally does not exceed 5% of the total material content on the entire current collector, but it has a great effect. It can enhance the conductivity of active materials, reduce internal resistance, and provide connections between active substances. It not only provides a conductive path, but also enhances the structural stability of the electrode. The large specific surface area can also increase the liquid absorption performance of the electrode, improve the ion transmission rate, and reduce polarization. This helps the active material achieve good capacity release and cycle stability, and improves the overall performance of the electrode and battery.
[0003] CN110137499A discloses a method for preparing a high-power lithium-ion battery conductive agent, wherein one or more aniline monomers, pyrrole monomers, thiophene monomers, and phenylene monomers are mixed in a template such as sodium dodecylbenzene sulfonate, and after polymerization is initiated by an initiator, a conductive agent material can be obtained after carbonization. The conductive agent has high electronic conductivity and ionic conductivity, and can significantly improve the high-rate charge and discharge capacity of lithium-ion batteries. CN106887591A discloses a composite conductive agent material composed of one or more of graphene and acetylene black, carbon black, graphite, carbon fiber, and carbon nanotubes, and the preparation method is simple and the conductive performance of the material is significantly improved. CN111916743A discloses a negative electrode composite conductive agent and a preparation method thereof, wherein the negative electrode composite conductive agent is composed of a first conductive agent, a second conductive agent and a dispersant, wherein the first conductive agent is nano-carbon fiber, the second conductive agent is any one of conductive carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, and conductive graphite, and the dispersant is any one or at least two of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl phosphate, hexadecyl trimethyl ammonium bromide, sodium polyacrylate, and sodium lignosulfonate. The composite conductive agent reduces the contact impedance between the particles of the negative electrode material through mutual synergy and excitation between the conductive agents, thereby improving the charge and discharge efficiency and service life of the negative electrode of the lithium ion battery. CN106099115A also discloses a method for preparing a composite conductive agent, wherein the conductive agent contains one or two of amino graphene and amino carbon nanotubes, and also contains 3-trimethyl-silane borate, which is used to reduce the interface impedance of the lithium ion battery, dissolve lithium fluoride, reduce the generation of inorganic products, improve the quality of SEI, and thus improve the high temperature cycle performance of the lithium ion battery. CN108649207A discloses a silicon quantum dot / carbon nanofiber composite conductive agent material, which uses electrostatic spinning technology to mix silicon quantum dots SiQDs into the micropores of carbon nanofibers CNFs, which can greatly improve the energy density, power density and cycle performance of the battery.
[0004] The above patents all study how to use two or more conductive agents to obtain composite conductive materials; however, whether carbon nanotubes, graphene or carbon nanofibers are used as conductive agents, or conductive polymers are carbonized to prepare conductive materials, compared with traditional conductive materials, the cost is relatively high and it is difficult to meet the actual application needs. Summary of the invention
[0005] The purpose of the present disclosure is to provide a conductive agent and a preparation method thereof, a negative electrode plate and a lithium ion battery. The conductive agent material is prepared by using gasified ash as a raw material, which has low cost and low usage.
[0006] In order to achieve the above object, the present disclosure provides a method for preparing a conductive agent in a first aspect, comprising the following steps:
[0007] S1. ball-milling gasified ash to obtain a first product, wherein the gasified ash includes ash produced in a heavy oil gasification process;
[0008] S2, performing a surface deacidification treatment on the first product to obtain a second product;
[0009] S3, calcining the second product.
[0010] Optionally, the gasified ash is prepared by removing metal from the ash raw material;
[0011] Preferably, the metal removal process is a hydrometallurgical metal recovery process; optionally, the conditions of the hydrometallurgical metal recovery process include:
[0012] The ash raw material is dried and dehydrated, and then crushed to a particle size of 20 to 60 μm to obtain a crushed ash raw material; the crushed ash raw material is mixed with an acid solution, and then acid hydrolyzed under stirring and reflux; the product obtained by the acid hydrolysis is filtered to obtain gasified ash from which metals have been removed;
[0013] Optionally, the acid solution is selected from one or more of hydrochloric acid, sulfuric acid and nitric acid, preferably sulfuric acid and / or hydrochloric acid; the mixing weight ratio of the acid solution to the crushed ash raw material is 2 to 10:1, preferably 2 to 5:1; Optionally, the stirring reflux temperature is room temperature or 45 to 100°C, and the acidolysis treatment time is 3 to 6 hours;
[0014] Optionally, the ash raw material is selected from one or more of vacuum residue gasification ash, residue hydrocracking tail oil gasification ash, deoiled asphalt gasification ash, catalytic oil slurry ash and ethylene tar ash;
[0015] Optionally, based on the total weight of the ash raw material, the C content in the ash raw material is 82-92 weight%, the H content is 1-10 weight%, the S content is 0.1-5 weight%, the N content is 0.1-5 weight%, the O content is 0.1-5 weight%, and the total content of impurity metals is 0.1-5 weight%, and the impurity metals include Ni, Mo, V, Fe, Na and Ga;
[0016] Preferably, based on the total weight of the gasified ash obtained after metal removal treatment, the C content in the gasified ash obtained after metal removal treatment is 84-92 weight%, the H content is 1-6 weight%, the S content is 0.1-5 weight%, the N content is 0.1-3 weight%, the O content is 0.1-5 weight%, and the total content of impurity metals is 0.1-3 weight%.
[0017] Optionally, in step S1, the ball milling treatment includes dry ball milling treatment and / or wet ball milling treatment; preferably, wet ball milling treatment;
[0018] Optionally, the conditions of the dry ball milling treatment include: a ball milling speed of 200 to 450 rpm, preferably 250 to 350 rpm; a ball milling time of 1 to 8 hours, preferably 2 to 6 hours; a ball milling temperature of 10 to 50° C., preferably 20 to 40° C.; a ball to material ratio of 1 to 40, preferably 10 to 30;
[0019] Optionally, the conditions of the wet ball milling treatment include: a ball milling speed of 200 to 1000 rpm, preferably 300 to 800 rpm; a ball milling time of 0.5 to 12 h, preferably 2 to 6 h; a ball milling temperature of 10 to 50° C., preferably 20 to 40° C.; a ball-to-material ratio of 1 to 40, preferably 10 to 30; relative to 1 g of the gasified ash, the amount of ball milling solvent is 10 to 200 mL, preferably 20 to 100 mL; optionally, the ball milling solvent is selected from one or more of ethanol, nitrogen methyl pyrrolidone, cyclohexane, cyclopentane sulfone and tetrahydrofuran.
[0020] Optionally, step S2 further includes:
[0021] The first product is subjected to a spray drying treatment, and then subjected to the surface acid removal treatment;
[0022] Optionally, the conditions of the spray drying process include: a feed temperature of 120 to 200° C., an outlet temperature of 80 to 100° C., a carrier gas flow rate of 12 to 20 L / min, an inlet pressure of 0.3 to 0.8 MPa, and the carrier gas is selected from one or more of nitrogen and argon;
[0023] Preferably, the feed temperature is 140-190° C., the outlet temperature is 90-100° C., the carrier gas flow rate is 14-18 L / min, and the inlet pressure is 0.4-0.6 MPa.
[0024] Optionally, in step S2, the surface acid removal treatment includes water washing treatment or alkali washing treatment; the water washing treatment and alkali washing treatment are independently carried out by stirring washing or ultrasonic washing;
[0025] Optionally, the conditions of the water washing treatment include: contacting the first product with deionized water, and then stirring and filtering to obtain a filter residue; repeating the process for more than 3 times to obtain a second product; Optionally, the weight ratio of deionized water to the first product is 1 to 50:1, preferably 10 to 20:1; the conditions of the stirring treatment include: a stirring speed of 100 to 1000 rpm, a stirring time of 2 to 12 h, preferably, a stirring speed of 200 to 400 rpm, and a stirring time of 4 to 8 h;
[0026] Optionally, the conditions of the alkali washing treatment include: the concentration of the alkali solution is 0.1 to 10 mol / L, preferably 0.1 to 5 mol / L; preferably, the alkali solution is selected from an aqueous solution of an alkali; the alkali is selected from one or more of sodium hydroxide, potassium hydroxide, sodium bicarbonate and sodium carbonate; the weight ratio of the alkali solution to the first product is 1 to 50:1, preferably 10 to 20:1;
[0027] Optionally, when stirring cleaning is adopted, the stirring temperature is 20-60°C, the stirring speed is 200-600rpm, and the stirring time is 1-12h; preferably, the stirring temperature is 20-40°C, the stirring speed is 200-450rpm, and the stirring time is 2-6h;
[0028] Optionally, when ultrasonic cleaning is adopted, the ultrasound is carried out in a closed constant temperature environment, the ultrasound time is 3 to 8 hours, the ultrasound power is 600 to 3000 W, and the ultrasound frequency is 20 to 80 KHz; preferably, the ultrasound time is 3 to 7 hours, the ultrasound power is 400 to 1000 W, and the ultrasound frequency is 40 to 60 KHz.
[0029] Optionally, the method further comprises: performing solid-liquid separation on the product obtained by the surface acid removal treatment to obtain a solid product; performing freeze-drying on the solid product to obtain the second product;
[0030] Optionally, the freeze-drying treatment conditions include: temperature of -80°C to -20°C, preferably -60°C to -30°C, time of 24 to 96 hours, preferably 48 to 72 hours, vacuum degree of 0.1 to 100 Pa, preferably 1 to 10 Pa.
[0031] Optionally, in step S3, the conditions for the calcination treatment include:
[0032] In an inert gas atmosphere, the temperature is raised to 600-1500° C., preferably, the temperature is raised to 750-1200° C.; the insulation time is 1-6 hours, preferably 2-4 hours; preferably, the heating rate is 0.5-5° C. / min, preferably 0.5-3° C. / min.
[0033] A second aspect of the present disclosure provides a conductive agent prepared according to the method of the first aspect of the present disclosure.
[0034] Optionally, based on the total weight of the conductive agent, the carbon content is greater than 88 weight %, the hydrogen content is less than 4 weight %, and the content of other impurity elements is less than 8 weight %, wherein the other impurity elements include one or more of sulfur, nitrogen, oxygen and impurity metals, and the impurity metals include Ni, Mo, V, Fe, Na and Ga;
[0035] Preferably, the powder conductivity of the conductive agent is 0.1 to 100 S / cm, preferably 1 to 20 S / cm;
[0036] Optionally, the conductive agent has a D 50 The particle size is 0.01-100 μm, the average pore size is 0.1-30 nm, and the BET specific surface area is 1-1000 m 2 / g, total pore volume 0.1~10cm 3 / g; preferably, the average particle size of the conductive agent is 1 to 50 μm, the average pore size is 0.5 to 18 nm, and the BET specific surface area is 5 to 200 m 2 / g, total pore volume is 0.1~1.5cm 3 / g.
[0037] A third aspect of the present disclosure provides a negative electrode plate, comprising the conductive agent described in the second aspect of the present disclosure.
[0038] Optionally, the negative electrode sheet is prepared by a method comprising the following steps: preparing a negative electrode slurry with the conductive agent and the negative electrode active material, coating the slurry on the surface of the negative electrode current collector, and drying the slurry;
[0039] Preferably, the negative electrode slurry comprises the conductive agent, the negative electrode active material, the dispersant and the binder;
[0040] Preferably, the weight ratio of the conductive agent: negative electrode active material: dispersant: binder is 1:18-90:0.3-4:0.4-5; preferably 1:30-60:0.5-2:0.5-2;
[0041] Optionally, the negative electrode active material is selected from one or more of carbon-based active particles and silicon-based particles; optionally, the carbon-based active particles are selected from one or more of soft carbon, hard carbon, artificial graphite, natural graphite and mesophase carbon microspheres; the silicon-based particles are selected from one or more of pure silicon nanomaterials, silicon-carbon composite materials and SiOx / C composite materials, wherein 0.3 <x<1.6;
[0042] The dispersant is selected from one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose, sodium alginate, polyvinyl alcohol, chitosan and β-cyclodextrin;
[0043] The binder is selected from one or more of styrene butadiene copolymer, polyacrylic acid, sodium polyacrylate, polyimide, polyvinylidene fluoride, nitrile rubber, butadiene rubber, xanthan gum and gum arabic.
[0044] A fourth aspect of the present disclosure provides a lithium-ion battery, which includes a positive electrode plate, the negative electrode plate described in the third aspect of the present disclosure, a battery separator, and an electrolyte.
[0045] Through the above technical scheme, the present disclosure provides a conductive agent and a preparation method thereof, a negative electrode plate and a lithium ion battery. The present disclosure uses gasified ash as a raw material to prepare the conductive agent material, which is not only low in cost but also low in usage, and has good industrial application prospects; the conductive agent provided by the present disclosure has low cost, high carbon content, strong conductivity, and large specific surface area, and can be used as a good conductive agent material. The conductive agent material can be used in combination with a variety of existing negative electrode active materials and has good compatibility.
[0046] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0048] Figure 1 This is a scanning electron microscope image of the conductive agent material provided in Example 1 of the present disclosure;
[0049] Figure 2 A nitrogen adsorption-desorption curve diagram of the conductive agent material provided in Example 1 of the present disclosure;
[0050] Figure 3 A pore size distribution diagram of the conductive agent material provided in Example 1 of the present disclosure;
[0051] Figure 4 The battery cycle performance diagram of the embodiments and comparative examples of the present disclosure. DETAILED DESCRIPTION
[0052] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.
[0053] According to the present disclosure, most of the conductive materials used in the field of lithium-ion batteries are acetylene carbon black or high-conductivity carbon black represented by SuperP-Li, with mature technology and relatively stable prices. However, carbon black is a point-shaped conductive agent, and the contact between active particles is point contact, with small conductivity and specific surface area. In order to adapt to the development of high-capacity battery materials, it is necessary to develop and adopt new conductive agent materials. Conductive agents such as conductive carbon fibers and carbon nanotubes with one-dimensional linear structures increase the contact sites between electrode material particles, greatly improve the conductivity between particles, and thus reduce the electrode sheet resistance. Graphene with a two-dimensional lamellar structure can make the contact between electrode particles become surface contact, improve the conductivity between particles, and reduce the amount of conductive agent, thereby improving the energy density of lithium-ion batteries. However, these new conductive agents are nano-sized, and are easily agglomerated and difficult to disperse due to the nano-size effect, and the cost of use is relatively high. The inventors of the present disclosure found that the use of gasified ash carbon material as a conductive agent material not only has a large specific surface area, but also is relatively easy to disperse, and is a good conductive agent for lithium-ion battery negative electrode materials.
[0054] The first aspect of the present disclosure provides a method for preparing a conductive agent, comprising the following steps:
[0055] S1. ball-milling gasified ash to obtain a first product, wherein the gasified ash includes ash produced in a heavy oil gasification process;
[0056] S2, performing a surface deacidification treatment on the first product to obtain a second product;
[0057] S3, calcining the second product.
[0058] The present disclosure provides a method for preparing a conductive agent, which uses gasified ash as a raw material to prepare a conductive agent material, which is not only low in cost, but also low in usage, and has good industrial application prospects; the conductive agent provided by the present disclosure has low cost, high carbon content, strong conductivity, and large specific surface area, and can be used as a good conductive agent material. The conductive agent material can be used in combination with a variety of existing negative electrode active materials and has good compatibility.
[0059] In a preferred embodiment, the gasified ash is prepared by removing metal from the ash raw material. Using the gasified ash after metal removal is conducive to avoiding the influence of impurity metals on the performance of the conductive agent and reducing the performance of the negative electrode plate.
[0060] In a specific embodiment, the ash raw material is selected from one or more of vacuum residue gasification ash, residue hydrocracking tail oil gasification ash, deoiled asphalt gasification ash, catalytic oil slurry ash and ethylene tar ash; preferably, deoiled asphalt or catalytic oil slurry gasification ash is used as the raw material of the conductive agent material;
[0061] Optionally, based on the total weight of the ash raw material, the C content in the ash raw material is 82-92 weight%, the H content is 1-10 weight%, the S content is 0.1-5 weight%, the N content is 0.1-5 weight%, the O content is 0.1-5 weight%, and the total content of impurity metals is 0.1-5 weight%, and the impurity metals include Ni, Mo, V, Fe, Na and Ga;
[0062] Preferably, based on the total weight of the gasified ash obtained after metal removal treatment, the C content in the gasified ash obtained after metal removal treatment is 84-92 weight%, the H content is 1-6 weight%, the S content is 0.1-5 weight%, the N content is 0.1-3 weight%, the O content is 0.1-5 weight%, and the total content of impurity metals is 0.1-3 weight%.
[0063] In a specific embodiment, the metal removal process is a hydrometallurgical metal recovery process; optionally, the conditions of the hydrometallurgical metal recovery process include:
[0064] The ash raw material is dried and dehydrated, and then crushed to a particle size of 20 to 60 μm to obtain a crushed ash raw material; the crushed ash raw material is mixed with an acid solution, and then acid hydrolyzed under stirring and reflux; the product obtained by the acid hydrolysis is filtered to obtain gasified ash from which metals have been removed;
[0065] Optionally, the acid solution is selected from one or more of hydrochloric acid, sulfuric acid and nitric acid, preferably sulfuric acid and / or hydrochloric acid; the mixing weight ratio of the acid solution to the crushed ash raw material is 2 to 10:1, preferably 2 to 5:1; optionally, the stirring reflux temperature is room temperature or 45 to 100°C, and the acidolysis treatment time is 3 to 6 hours.
[0066] In one embodiment, in step S1, the ball milling treatment includes dry ball milling treatment and / or wet ball milling treatment; the ball milling jar and the ball milling beads may be made of zirconium oxide. Preferably, the gasification ash is treated by a wet method.
[0067] In one embodiment, the conditions for the dry ball milling treatment include: a ball milling speed of 200 to 450 rpm, preferably 250 to 350 rpm; a ball milling time of 1 to 8 hours, preferably 2 to 6 hours; a ball milling temperature of 10 to 50° C., preferably 20 to 40° C.; and a ball-to-material ratio of 1 to 40, preferably 10 to 30.
[0068] In one embodiment, the conditions of the wet ball milling treatment include: a ball milling speed of 200 to 1000 rpm, preferably 300 to 800 rpm; a ball milling time of 0.5 to 12 h, preferably 2 to 6 h; a ball milling temperature of 10 to 50° C., preferably 20 to 40° C.; a ball-to-material ratio of 1 to 40, preferably 10 to 30; relative to 1 g of the gasified ash, the amount of ball milling solvent is 10 to 200 mL, preferably 20 to 100 mL; optionally, the ball milling solvent is selected from one or more of ethanol, nitrogen methyl pyrrolidone, cyclohexane, cyclopentane sulfone and tetrahydrofuran.
[0069] In the present disclosure, the gasification ash is ball-milled to break it into small particles, thereby increasing the conductive sites of the ash and exposing more acid sites to facilitate subsequent cleaning.
[0070] In one implementation, step S2 further includes:
[0071] The first product is subjected to a spray drying treatment, and then subjected to the surface acid removal treatment;
[0072] Optionally, the conditions for the spray drying treatment include: a feed temperature of 120-200°C; an outlet temperature of 80-100°C; a carrier gas flow rate of 12-20 L / min, an inlet pressure of 0.3-0.8 MPa, and the carrier gas is selected from one or more of nitrogen and argon.
[0073] In a preferred embodiment, the conditions of the spray drying process include: a feed temperature of 140 to 190° C.; an outlet temperature of 90 to 100° C.; a carrier gas flow rate of 14 to 18 L / min, and a pressure of 0.4 to 0.6 MPa.
[0074] In one embodiment, in step S2, the surface deacidification treatment includes water washing treatment or alkali washing treatment; the water washing treatment and alkali washing treatment are independently carried out by stirring washing or ultrasonic washing; preferably, alkali washing is used for surface treatment.
[0075] In one embodiment, the conditions of the water washing treatment include: the weight ratio of deionized water to the gasified ash after metal removal (first product) is 1 to 50:1, preferably 10 to 20:1; the gasified ash after metal removal is added to the deionized water, and stirred at a speed of 100 to 1000 rpm for 2 to 12 hours, preferably, the stirring speed is 200 to 400 rpm, and the stirring time is 4 to 8 hours; then the mixed liquid is filtered to obtain a filter residue, and the above steps are repeated 3 times to obtain the gasified ash after water treatment;
[0076] Optionally, the conditions for the alkali washing treatment include: the concentration of the alkali solution is 0.1 to 10 mol / L, preferably 0.1 to 5 mol / L; preferably, the alkali solution is selected from an aqueous solution of an alkali; the alkali is selected from one or more of sodium hydroxide, potassium hydroxide, sodium bicarbonate and sodium carbonate; the weight ratio of the alkali solution to the first product is 1 to 50:1, preferably 10 to 20:1.
[0077] In a specific embodiment, when stirring cleaning is adopted during water washing or alkali washing, the stirring temperature is 20-60°C, the stirring speed is 200-600rpm, and the stirring time is 1-12h; preferably, the stirring temperature is 20-40°C, the stirring speed is 200-450rpm, and the stirring time is 2-6h; when ultrasonic cleaning is adopted during water washing or alkali washing, closed constant temperature ultrasound, ultrasonic time is 3-8h, ultrasonic power is 600-3000W, and ultrasonic frequency is 20-80KHz; preferably, ultrasonic time is 3-7h, ultrasonic power is 400-1000W, and ultrasonic frequency is 40-60KHz.
[0078] In one embodiment, the method further comprises: performing solid-liquid separation on the product obtained by the surface acid removal treatment to obtain a solid product; performing freeze-drying on the solid product to obtain the second product;
[0079] Optionally, the freeze-drying treatment conditions include: temperature of -80°C to -20°C, preferably -60°C to -30°C, time of 24 to 96 hours, preferably 48 to 72 hours, vacuum degree of 0.1 to 100 Pa, preferably 1 to 10 Pa.
[0080] In one embodiment, in step S3, the conditions for the calcination treatment include:
[0081] In an inert gas atmosphere, the temperature is raised to 600-1500° C., preferably, the temperature is raised to 750-1200° C.; the heat preservation time is 1-6 hours, preferably 2-4 hours;
[0082] Preferably, the heating rate is 0.5 to 5°C / min, preferably 0.5 to 3°C / min.
[0083] In a specific embodiment, the inert atmosphere comprises one or more of nitrogen, helium, and argon; the water content of the inert atmosphere is less than 0.1 wt%, and the oxygen content is less than 0.1 wt%.
[0084] A second aspect of the present disclosure provides a conductive agent prepared according to the method described in the first aspect of the present disclosure.
[0085] In one embodiment, based on the total weight of the conductive agent, the carbon content is 88 wt% or more, the hydrogen content is 4 wt% or less, and the content of other impurity elements is 8 wt% or less. The other impurity elements include one or more of sulfur, nitrogen, oxygen, and impurity metals (including Ni, Mo, V, Fe, Na, Ga, etc.).
[0086] In one embodiment, the powder conductivity of the conductive agent is 0.1 - 100 S / cm, preferably 1 - 20 S / cm;
[0087] Optionally, the D 50 particle size of the conductive agent is 0.01 - 100 μm, the average pore diameter is 0.1 - 30 nm, the BET specific surface area is 1 - 1000 m 2 / g, and the total pore volume is 0.1 - 10 cm 3 / g; preferably, the average particle size of the conductive agent is 1 - 50 μm, the average pore diameter is 0.5 - 18 nm, the BET specific surface area is 5 - 200 m 2 / g, and the total pore volume is 0.1 - 1.5 cm 3 / g.
[0088] The third aspect of the present disclosure provides a negative electrode sheet including the conductive agent described in the second aspect of the present disclosure.
[0089] In a specific embodiment, the negative electrode sheet is prepared by a method including the following steps: making a negative electrode slurry from the conductive agent and a negative electrode active material, and then coating it on the surface of a negative electrode current collector and performing a drying treatment.
[0090] In one embodiment, the negative electrode slurry includes the conductive agent, a negative electrode active material, a dispersant, and a binder;
[0091] Preferably, the weight ratio of the conductive agent: negative electrode material: dispersant: binder is 1:18 - 90:0.3 - 4:0.4 - 5; preferably 1:30 - 60:0.5 - 2:0.5 - 2.
[0092] In a specific embodiment, the negative electrode material is selected from one or more of carbon-based active particles and silicon-based particles; optionally, the carbon-based active particles are selected from one or more of soft carbon, hard carbon, artificial graphite, natural graphite, and mesophase carbon microspheres; the silicon-based particles are selected from one or more of pure silicon nanomaterials, silicon-carbon composites, and SiOx / C (0.3 < x < 1.6) composites;
[0093] The dispersant is selected from one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose, sodium alginate, polyvinyl alcohol, chitosan, and β-cyclodextrin;
[0094] The binder is selected from one or more of styrene butadiene copolymer (styrene butadiene rubber), polyacrylic acid, sodium polyacrylate, polyimide, polyvinylidene fluoride, nitrile rubber, butadiene rubber, xanthan gum and gum arabic.
[0095] The negative electrode material, dispersant and binder in the negative electrode slurry disclosed in the present invention can be purchased through common commercial channels, or prepared by known methods.
[0096] In a specific embodiment, the negative electrode slurry is made into a negative electrode by the following method: (1) First weigh 80 to 97 parts by weight of the negative electrode active material and 1 to 10 parts by weight of the above-mentioned conductive agent and mechanically mix them. (2) Then weigh 1 to 5 parts by weight of a CMC (carboxymethyl cellulose) solution with a mass fraction of 1 to 3% by weight and add it to the powder, mix it in a homogenizer at a speed of 700 to 3000 rpm for 5 to 30 minutes, during which the slurry on the wall is scraped off, stirred and mixed again, and deionized water is added twice in total to a total of 100 parts by weight. (3) After mixing evenly, add 1 to 5 parts by weight of a 10% by weight SBR emulsion (styrene butadiene emulsion), and continue to mix in the homogenizer at a speed of 700 to 3000 rpm for 5 to 30 minutes. (4) After the slurry is mixed evenly, observe the fluidity, and the slurry can flow without stratification. (5) The negative electrode slurry is coated on the current collector copper foil, and the negative electrode sheet can be obtained by drying and rolling. The final pole piece single surface density is 4mg / cm 2 ~12mg / cm 2 , compacted density 1.10g / cm 3 ~1.80g / cm 3 .
[0097] A fourth aspect of the present disclosure provides a lithium-ion battery, which includes a positive electrode plate, the negative electrode plate described in the third aspect of the present disclosure, a battery separator, and an electrolyte.
[0098] In a specific embodiment, the negative electrode plate of the lithium ion battery includes a silicon-carbon negative electrode plate; the capacity ratio of the negative electrode plate to the positive electrode plate is 1.1 to 1.2:1; and the lithium ion battery is a button lithium ion battery, a cylindrical lithium ion battery or a square lithium ion battery.
[0099] The positive electrode, electrolyte and separator of the lithium ion battery provided by the present disclosure can be various materials conventionally adapted in the art, and the present disclosure has no particular limitation on this. For example, the separator can be selected from any one of polyethylene film, polypropylene film and cellulose film, the positive electrode can be selected from lithium iron phosphate, lithium cobalt oxide, and ternary positive electrode, and the electrolyte can be lithium hexafluorophosphate dissolved in a carbonate mixed solvent.
[0100] The present disclosure is further described in detail below through examples. The raw materials used in the examples can all be obtained through commercial channels.
[0101] The particle size was measured using an optical particle size analyzer, the instrument model being Mastersizer 3000;
[0102] The nitrogen adsorption-desorption curve, average pore size, BET specific surface area and total pore volume test instrument and method are JW-BK200 series, static capacity method measurement;
[0103] The SEM test method is scanning electron microscope, and the instrument model is S4800 of Hitachi, Japan;
[0104] The XRD test method is an X-ray diffractometer, and the instrument model is the X'Pert PRO powder X-ray diffractometer from PANalytical;
[0105] The XPS test method is X-ray photoelectron spectrometer, and the instrument model is VG ESCALAB;
[0106] The test method for electrochemical cycle performance is the blue electric test system, and the instrument model is CT3001A.
[0107] In the following examples, the examples numbered as "Example A" series are used to illustrate the preparation of conductive agents; and the examples numbered as "Example B" series are used to illustrate the preparation of negative electrodes.
[0108] Example A1
[0109] (1) The asphalt ash raw material used in this embodiment (based on the total weight of the asphalt ash raw material, the C content in the ash raw material is 84% by weight, the H content is 5% by weight, the S content is 3% by weight, the N content is 0.5% by weight, the O content is 5% by weight, and the total content of impurity metals is 2.5% by weight), and the ash raw material is subjected to hydrometallurgical metal recovery treatment, specifically comprising: drying and dehydrating the asphalt ash raw material and then crushing it to a particle size of 20 to 60 μm; using 1 mol / L sulfuric acid is mixed with the gasification ash in a mass ratio of 4:1, and then stirred at room temperature, acid hydrolyzed for 4 hours, and filtered after acid hydrolysis to obtain the gasification ash after metal removal. Based on the total weight of the gasification ash obtained after metal removal, the gasification ash obtained after metal removal has a C content of 86.0% by weight, a H content of 5.0% by weight, a S content of 3.2% by weight, a N content of 0.5% by weight, an O content of 4.8% by weight, and a total impurity metal content of 0.5% by weight;
[0110] (2) Take 5g of the asphalt gasification ash after metal removal and disperse it in 100mL of ethanol. Mix them evenly. For every 1g of gasification ash, the amount of ball milling solvent is 20mL. Put the above mixture into a 500mL zirconia ball mill jar, add 75g of 1mm zirconia beads, and the ball-to-material ratio is 15. Place it on a planetary ball mill, set the ball mill speed to 450rpm, the time to 6h, and the temperature to 30℃.
[0111] (3) After ball milling, the suspension liquid was spray dried. The spray drying conditions were as follows: inlet temperature (feed temperature) of 170°C, outlet temperature of 90°C, feed rate of 10 ml / min, carrier gas flow rate of 15 L / min, inlet pressure of 0.5 MPa, and carrier gas of nitrogen.
[0112] (4) Collect the powder after spray drying, put it into a 300 ml beaker, add 100 ml of 0.5 mol / L potassium hydroxide solution, mix well, and the weight ratio of alkali solution to dried powder is 20:1. Then use a magnetic stirrer to stir the mixed liquid for alkali washing. The stirring conditions are: room temperature, rotation speed of 400 rpm, and stirring time of 8 hours.
[0113] (5) After alkali washing, the material is filtered and then dried by freeze drying. The temperature is set to -60°C, the time is 48 hours, and the vacuum degree is 8Pa.
[0114] (6) The freeze-dried powder was placed in an atmosphere furnace for calcination and carbonization. The calcination conditions were: in an Ar atmosphere, at atmospheric pressure (gauge pressure), the temperature was raised to 1200° C. at 3° C. / min, and the temperature was kept at this temperature for 2 h. Finally, the conductive agent material was obtained, which was recorded as J-1.
[0115] Figure 1 This is a scanning electron microscope (SEM) picture of the conductive agent material J-1 prepared in this example. It can be seen from the picture that the conductive agent has a flocculent structure, a porous surface, and a particle size in the range of 5 to 10 μm.
[0116] Figure 2 The nitrogen adsorption-desorption curve of the conductive material J-1 prepared in this example is shown in the figure. It can be seen from the figure that the adsorption-desorption curve is a type IV adsorption-desorption curve, and the mesoporous hysteresis loop belongs to the H3 type, indicating that the main pore structure of the conductive material is mainly a slit structure, a crack and a wedge structure formed by flake particles, which is different from Figure 1 The SEM image of the conductive agent material shown is consistent.
[0117] Figure 3 This is the pore size distribution diagram of the conductive material J-1 prepared in this example. It can be seen from the figure that the pore size of the conductive material is mainly concentrated in the range of 3 to 4.5 nm.
[0118] Example A2
[0119] This embodiment refers to the method of Example 1, and the difference from Example 1 is that the potassium hydroxide solution in step (4) is replaced with an equal volume of deionized water for washing, and the rest of the process is the same as Example 1. The prepared conductive agent is recorded as J-2.
[0120] Example A3
[0121] This embodiment refers to the method of Example 1, except that the speed of the ball mill in step (2) is changed to 800 rpm, and the rest of the process is the same as Example 1. The conductive agent prepared is recorded as J-3.
[0122] Example A4
[0123] This embodiment refers to the preparation method of embodiment 1, and the difference from embodiment 1 is that the type of ash raw material and the conditions for metal removal treatment are changed.
[0124] The vacuum residue gasification ash raw material used in this embodiment (based on the total weight of the vacuum residue gasification ash raw material, the C content of the vacuum residue gasification ash raw material is 87% by weight, the H content is 5.6% by weight, the S content is 2.3% by weight, the N content is 0.3% by weight, the O content is 3% by weight, and the total content of impurity metals is 1.8% by weight), and the ash raw material is subjected to hydrometallurgical metal recovery treatment. The specific operation is the same as step (1) in Example A1. Based on the total weight of the gasified ash obtained after the metal removal treatment, the C content of the gasified ash obtained after the metal removal treatment is 88.4% by weight, the H content is 5.3% by weight, the S content is 2.3% by weight, the N content is 0.3% by weight, the O content is 3.5% by weight, and the total content of impurity metals is 0.2% by weight. The rest of the process is the same as that of Example 1, and the prepared conductive agent is recorded as J-4.
[0125] Example A5
[0126] (1) This embodiment uses the same asphalt ash raw material as in the embodiment, and performs the same hydrometallurgical metal recovery treatment on the ash raw material;
[0127] (2) Take 5g of the asphalt gasification ash after metal removal and disperse it in 40mL of ethanol. Mix well. For every 1g of gasification ash, the amount of ball milling solvent is 8mL. Put the above mixture into a 500mL zirconia ball milling jar, add 75g of 1mm zirconia beads, and the ball-to-material ratio is 15. Place it on a planetary ball mill, set the ball mill speed to 100rpm, the time to 24h, and the temperature to 60℃.
[0128] (3) After ball milling, the suspension liquid was spray dried. The spray drying conditions were as follows: inlet temperature of 170°C, inlet pressure of 0.5 MPa, outlet temperature of 90°C, feed rate of 10 ml / min, carrier gas flow rate of 15 L / min, and carrier gas was nitrogen.
[0129] (4) Collect the powder after spray drying, put it into a 300 ml beaker, add 160 ml of 0.5 mol / L potassium hydroxide solution, mix well, and the weight ratio of alkali solution to dried powder is 80:1. Then use a magnetic stirrer to stir the mixed liquid for alkali washing. The stirring conditions are: room temperature, rotation speed of 400 rpm, and stirring time of 8 hours.
[0130] (5) After alkali washing, the material is filtered and then dried by freeze drying. The temperature is set to -76°C, the time is 36 hours, and the vacuum degree is 8Pa.
[0131] (6) The freeze-dried powder was placed in an atmosphere furnace for calcination and carbonization. The calcination conditions were: in an Ar atmosphere, at normal pressure, the temperature was raised to 500° C. at a rate of 10° C. / min, and the holding time was 5 h. Finally, the conductive agent material was obtained, which was recorded as J-5.
[0132] Example A6
[0133] (1) This embodiment uses the same asphalt ash raw material as in the embodiment, and performs the same hydrometallurgical metal recovery treatment on the ash raw material;
[0134] (2) Take 5 g of the asphalt gasification ash after metal removal and disperse it in 500 mL of ethanol. Mix them evenly. For every 1 g of gasification ash, the amount of ball milling solvent is 100 mL. Put the above mixture into a 500 mL zirconia ball mill jar, add 75 g of 1 mm zirconia beads, and the ball-to-material ratio is 15. Place it on a planetary ball mill, set the ball mill speed to 450 rpm, the time to 6 hours, and the temperature to 30°C.
[0135] (3) After ball milling, the suspension liquid was spray dried. The spray drying conditions were as follows: inlet temperature (feed temperature) of 170°C, outlet temperature of 90°C, feed rate of 10 ml / min, carrier gas flow rate of 15 L / min, inlet pressure of 0.5 MPa, and carrier gas of nitrogen.
[0136] (4) Collect the powder after spray drying, put it into a 300 ml beaker, add 100 ml of 0.5 mol / L potassium hydroxide solution, mix well, and the weight ratio of alkali solution to dried powder is 20:1. Then use a magnetic stirrer to stir the mixed liquid for alkali washing. The stirring conditions are: room temperature, rotation speed of 400 rpm, and stirring time of 6 hours.
[0137] (5) After alkali washing, the material is filtered and then dried by freeze drying with the temperature set at -60°C, the time at 48h and the vacuum degree at 8Pa.
[0138] (6) The freeze-dried powder was placed in an atmosphere furnace for calcination and carbonization. The calcination conditions were: in an Ar atmosphere, at atmospheric pressure (gauge pressure), the temperature was raised to 1200° C. at 3° C. / min, and the temperature was kept at this temperature for 2 h. Finally, the conductive agent material was obtained, which was recorded as J-6.
[0139] Example A7
[0140] This example refers to the preparation method in Example 1, and the difference from Example 1 is that:
[0141] In step (2), dry ball milling is adopted, which specifically includes: ball milling speed of 250 rpm, ball milling time of 6 h; ball milling temperature of 40° C.; ball-to-material ratio of 30; and the rest of the process is the same as in Example 1, and finally the conductive agent material is obtained, which is recorded as J-7.
[0142] Example A8
[0143] This example refers to the preparation method in Example 1, and the difference from Example 1 is that:
[0144] In step (4), the powder after spray drying is collected, put into a 300 ml beaker, 100 ml of 0.5 mol / L potassium hydroxide solution is added, and mixed evenly, and the weight ratio of the alkali solution to the dried powder is 20:1. Then, the mixed liquid is ultrasonically cleaned with an ultrasonic device to perform alkali cleaning, and the ultrasonic cleaning is performed at a closed constant temperature, the ultrasonic time is 6 hours, the ultrasonic power is 600 W, and the ultrasonic frequency is 40 KHz. The rest of the process is the same as in Example 1, and the conductive agent material is finally obtained, which is recorded as J-8.
[0145] Embodiment A9
[0146] This example refers to the preparation method in Example 1, and the difference from Example 1 is that:
[0147] In step (6), the freeze-dried powder is placed in an atmosphere furnace for calcination and carbonization. The calcination conditions are: in an Ar atmosphere, at a pressure of normal pressure (gauge pressure), the temperature is raised to 1500° C. at a rate of 5° C. / min, and then the temperature is kept for 1 hour. Finally, the conductive agent material is obtained, which is recorded as J-9.
[0148] Comparative Example A1
[0149] This comparative example refers to the preparation method of Example 1, which is different from Example 1 in that no alkali washing is performed, and the rest of the process is the same as Example 1. The prepared conductive agent is recorded as DA-1.
[0150] Comparative Example A2
[0151] This comparative example refers to the preparation method of Example 1, which is different from Example 1 in that no calcination treatment is performed, and the rest of the process is the same as Example 1. The conductive agent prepared is recorded as DA-2.
[0152] Comparative Example A3
[0153] The comparative example refers to the preparation method of Example 1, which is different from Example 1 in that the asphalt gasification ash is replaced by coal gasification ash, and the rest of the process is the same as Example 1. The prepared conductive agent is recorded as DA-3.
[0154] Embodiments B1 to B9
[0155] Conductive materials J-1 to J-9 were mixed with natural graphite negative electrode materials, CMC (dispersant) and SBR (binder) in a vacuum homogenizer at a mass ratio of 3:92:2:3 (i.e., a weight ratio of 1:30.7:0.67:1); then coated on a copper current collector and dried; finally, negative electrode sheets were obtained, which were respectively recorded as F-1 to F-9.
[0156] Example B10
[0157] The conductive material J-1 prepared in Example 1 was mixed with the natural graphite negative electrode material, CMC (dispersant) and SBR (binder) in a vacuum homogenizer at a mass ratio of 5:91:1.7:2.3 (i.e., 1:18.2:0.34:0.46). The rest of the process was the same as in Example B1, and finally a negative electrode sheet was obtained, which was recorded as F-10.
[0158] Example B11
[0159] The conductive material J-1 prepared in Example 1 was mixed with the natural graphite negative electrode material, CMC (dispersant) and SBR (binder) in a vacuum homogenizer at a mass ratio of 1.5:95:1.5:2.0 (i.e. 1:63.3:1:1.3). The rest of the process was the same as in Example B1, and finally a negative electrode sheet was obtained, which was recorded as F-11.
[0160] Comparative Examples B1 to B3
[0161] Referring to the preparation method in Example B1, the difference from Example B1 is that the conductive material J-1 is replaced by the conductive materials DA-1 to DA-3 prepared in the comparative example, and the rest of the process is the same as that in Example B1, and finally the negative electrode sheets are obtained, which are respectively recorded as DB-1 to DB-3.
[0162] The components and structural parameters of the conductive agent materials prepared in the above examples are listed in Table 1 below.
[0163] Table 1
[0164]
[0165]
[0166] Test Case
[0167] This test example is used to illustrate the electrochemical performance of the conductive agent and the negative electrode prepared in the above embodiments and comparative examples when applied to lithium-ion batteries.
[0168] The negative electrode sheet prepared in the embodiment and the comparative example was used as the negative electrode of the battery, the metal lithium sheet was used as the positive electrode, a Celgard 2325 model diaphragm and an electrolyte of 1 mol / L LiPF6 (the solvent volume ratio was ethylene carbonate: dimethyl carbonate: diethyl carbonate = 1:1:1) were selected to assemble into a button half-cell in a glove box.
[0169] The battery was charged and discharged using the Blue Electric system. The parameters were set as follows: current density was 0.1C for the first cycle, followed by a change in rate, and voltage range was 0.005 to 1.5V. The test results are listed in Table 2 below.
[0170] Table 2
[0171]
[0172]
[0173] From the data in Table 2 above, we can see that:
[0174] (1) By comparing the conductive materials J-1 and DA-1 prepared in Example A1 and Comparative Example A1, it can be found that the gasification ash needs to be subjected to surface deacidification treatment (alkali washing), which can greatly improve the initial coulombic efficiency of the material. Figure 4It can be seen that the electrode prepared by the conductive material in comparative example A1 has extremely poor cycle performance without surface deacidification treatment. After 100 cycles, the specific capacity is less than 100 mAh / g. Comparing the conductive agents J-1 and DA-2 to DA-3 prepared by Example A1 with those prepared by comparative examples A2 to A3, it can be seen that comparative example A2 does not perform calcination during the preparation process, and comparative example A3 uses coal gasification ash instead of asphalt gasification ash during the preparation process. Compared with the conductive agents DA-2 to DA-3 obtained in the comparative examples, the conductive agent J-1 prepared by Example A1 according to the method provided by the present disclosure can obtain higher first coulomb efficiency and cycle capacity retention rate.
[0175] (2) By comparing Example A1 with Comparative Example A2, it can be found that the conductive agent material of Comparative Example A2, which is not calcined and carbonized, has lower capacity performance and first coulombic efficiency. The conductive agent prepared by the method provided in Example A1 has higher first coulombic efficiency and cycle capacity retention rate.
[0176] (3) The amount of the conductive material J-1 used in Example B11 was reduced to 1.5% by weight. Figure 4 It can be seen that the capacity retention rate of the negative electrode provided in Example B11 is low under high rate conditions. In Example B10, the amount of conductive material J-1 used is increased to 5.0% by weight, combined with Figure 4 It is found that the capacity of Example B10 decreases under high rate conditions. Therefore, by comparing Example B1 with Examples B10 to B11, it can be seen that Example B1 prepares the negative electrode slurry according to the weight ratio provided in the present disclosure, and the negative electrode obtained can take into account both the first coulombic efficiency and the cycle performance.
[0177] (4) The conductive agent J-2 in Example A2 was washed with water during the preparation process, and the conductive agent J-1 in Example A1 was washed with alkali during the preparation process. The first coulombic efficiency of J-2 was lower than that of J-1, and the effect of J-1 was better than that of J-2.
[0178] (5) By comparing Example A1 with Example A5, it can be seen that Example A1 prepares the conductive agent material according to the optimized conditions of the present disclosure during the preparation process. Compared with the conductive agent J-5 prepared by Example A5, the conductive agent J-1 prepared by Example A1 can obtain higher first coulombic efficiency and cycle capacity retention rate.
[0179] (6) By comparing Example A1 with Example A9, it can be seen that in the preparation process of Example A1, the conductive agent is prepared according to the optimized carbonization roasting conditions of "heating rate of 0.5 to 3°C / min, heating to 750 to 1200°C, and keeping warm for 2 to 4 hours". Compared with the conductive agent J-1 obtained in Example A9, the conductive agent J-1 obtained in Example A1 can have higher first coulombic efficiency and cycle capacity retention rate.
[0180] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0181] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0182] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A method for preparing a conductive agent, characterized in that: The following steps are involved: S1. ball-milling gasified ash to obtain a first product, wherein the gasified ash includes ash produced in a heavy oil gasification process; S2, performing a surface deacidification treatment on the first product to obtain a second product; S3, calcining the second product.
2. The method according to claim 1, characterized in that The gasified ash is prepared by removing metal from the ash raw material; Preferably, the metal removal process is a hydrometallurgical metal recovery process; optionally, the conditions of the hydrometallurgical metal recovery process include: The ash raw material is dried and dehydrated, and then crushed to a particle size of 20 to 60 μm to obtain a crushed ash raw material; the crushed ash raw material is mixed with an acid solution, and then acid hydrolyzed under stirring and reflux; the product obtained by the acid hydrolysis is filtered to obtain gasified ash from which metals have been removed; Optionally, the acid solution is selected from one or more of hydrochloric acid, sulfuric acid and nitric acid, preferably sulfuric acid and / or hydrochloric acid; the mixing weight ratio of the acid solution to the crushed ash raw material is 2 to 10:1, preferably 2 to 5:1; Optionally, the stirring reflux temperature is room temperature or 45 to 100°C, and the acidolysis treatment time is 3 to 6 hours; Optionally, the ash raw material is selected from one or more of vacuum residue gasification ash, residue hydrocracking tail oil gasification ash, deoiled asphalt gasification ash, catalytic oil slurry ash and ethylene tar ash; Optionally, based on the total weight of the ash raw material, the C content in the ash raw material is 82-92 weight%, the H content is 1-10 weight%, the S content is 0.1-5 weight%, the N content is 0.1-5 weight%, the O content is 0.1-5 weight%, and the total content of impurity metals is 0.1-5 weight%, and the impurity metals include Ni, Mo, V, Fe, Na and Ga; Preferably, based on the total weight of the gasified ash obtained after metal removal treatment, the C content in the gasified ash obtained after metal removal treatment is 84-92 weight%, the H content is 1-6 weight%, the S content is 0.1-5 weight%, the N content is 0.1-3 weight%, the O content is 0.1-5 weight%, and the total content of impurity metals is 0.1-3 weight%.
3. The method according to claim 1, characterized in that In step S1, the ball milling process includes dry ball milling process and / or wet ball milling process; preferably, wet ball milling process; Optionally, the conditions of the dry ball milling treatment include: a ball milling speed of 200 to 450 rpm, preferably 250 to 350 rpm; a ball milling time of 1 to 8 hours, preferably 2 to 6 hours; a ball milling temperature of 10 to 50° C., preferably 20 to 40° C.; a ball to material ratio of 1 to 40, preferably 10 to 30; Optionally, the conditions of the wet ball milling treatment include: a ball milling speed of 200 to 1000 rpm, preferably 300 to 800 rpm; a ball milling time of 0.5 to 12 h, preferably 2 to 6 h; a ball milling temperature of 10 to 50° C., preferably 20 to 40° C.; a ball-to-material ratio of 1 to 40, preferably 10 to 30; relative to 1 g of the gasified ash, the amount of ball milling solvent is 10 to 200 mL, preferably 20 to 100 mL; optionally, the ball milling solvent is selected from one or more of ethanol, nitrogen methyl pyrrolidone, cyclohexane, cyclopentane sulfone and tetrahydrofuran.
4. The method according to claim 1, characterized in that: Step S2 also includes: The first product is subjected to a spray drying treatment, and then subjected to the surface acid removal treatment; Optionally, the conditions of the spray drying process include: a feed temperature of 120 to 200° C., an outlet temperature of 80 to 100° C., a carrier gas flow rate of 12 to 20 L / min, an inlet pressure of 0.3 to 0.8 MPa, and the carrier gas is selected from one or more of nitrogen and argon; Preferably, the feed temperature is 140-190° C., the outlet temperature is 90-100° C., the carrier gas flow rate is 14-18 L / min, and the inlet pressure is 0.4-0.6 MPa.
5. The method according to claim 1, characterized in that In step S2, the surface acid removal treatment includes water washing treatment or alkali washing treatment; the water washing treatment and alkali washing treatment are independently carried out by stirring washing or ultrasonic washing; Optionally, the conditions of the water washing treatment include: contacting the first product with deionized water, and then stirring and filtering to obtain a filter residue; repeating the process for more than 3 times to obtain a second product; Optionally, the weight ratio of deionized water to the first product is 1 to 50:1, preferably 10 to 20:1; the conditions of the stirring treatment include: a stirring speed of 100 to 1000 rpm, a stirring time of 2 to 12 h, preferably, a stirring speed of 200 to 400 rpm, and a stirring time of 4 to 8 h; Optionally, the conditions of the alkali washing treatment include: the concentration of the alkali solution is 0.1 to 10 mol / L, preferably 0.1 to 5 mol / L; preferably, the alkali solution is selected from an aqueous solution of an alkali; the alkali is selected from one or more of sodium hydroxide, potassium hydroxide, sodium bicarbonate and sodium carbonate; the weight ratio of the alkali solution to the first product is 1 to 50:1, preferably 10 to 20:1; Optionally, when stirring cleaning is adopted, the stirring temperature is 20-60°C, the stirring speed is 200-600rpm, and the stirring time is 1-12h; preferably, the stirring temperature is 20-40°C, the stirring speed is 200-450rpm, and the stirring time is 2-6h; Optionally, when ultrasonic cleaning is adopted, the ultrasound is carried out in a closed constant temperature environment, the ultrasound time is 3 to 8 hours, the ultrasound power is 600 to 3000 W, and the ultrasound frequency is 20 to 80 KHz; preferably, the ultrasound time is 3 to 7 hours, the ultrasound power is 400 to 1000 W, and the ultrasound frequency is 40 to 60 KHz.
6. The method according to claim 5, characterized in that The method further comprises: performing solid-liquid separation on the product obtained by the surface acid removal treatment to obtain a solid product; performing freeze-drying on the solid product to obtain the second product; Optionally, the freeze-drying treatment conditions include: temperature of -80°C to -20°C, preferably -60°C to -30°C, time of 24 to 96 hours, preferably 48 to 72 hours, vacuum degree of 0.1 to 100 Pa, preferably 1 to 10 Pa.
7. The method according to claim 1, characterized in that In step S3, the conditions of the calcination treatment include: In an inert gas atmosphere, the temperature is raised to 600-1500° C., preferably, the temperature is raised to 750-1200° C.; the insulation time is 1-6 hours, preferably 2-4 hours; preferably, the heating rate is 0.5-5° C. / min, preferably 0.5-3° C. / min.
8. The conductive agent prepared by the method according to any one of claims 1 to 7.
9. The conductive agent according to claim 8, characterized in that: Based on the total weight of the conductive agent, the carbon content is 88 weight % or more, the hydrogen content is 4 weight % or less, and the content of other impurity elements is 8 weight % or less, wherein the other impurity elements include one or more of sulfur, nitrogen, oxygen and impurity metals, and the impurity metals include Ni, Mo, V, Fe, Na and Ga; Preferably, the powder conductivity of the conductive agent is 0.1 to 100 S / cm, preferably 1 to 20 S / cm; Optionally, the conductive agent has a D 50 The particle size is 0.01-100 μm, the average pore size is 0.1-30 nm, and the BET specific surface area is 1-1000 m 2 / g, total pore volume 0.1~10cm 3 / g; preferably, the average particle size of the conductive agent is 1 to 50 μm, the average pore size is 0.5 to 18 nm, and the BET specific surface area is 5 to 200 m 2 / g, total pore volume is 0.1~1.5cm 3 / g.
10. A negative electrode plate, characterized in that: Contains the conductive agent described in claim 8 or 9.
11. The negative electrode sheet according to claim 10, characterized in that: The negative electrode sheet is prepared by a method comprising the following steps: preparing a negative electrode slurry with the conductive agent and the negative electrode active material, coating the slurry on the surface of the negative electrode current collector, and drying the slurry; Preferably, the negative electrode slurry comprises the conductive agent, the negative electrode active material, the dispersant and the binder; Preferably, the weight ratio of the conductive agent: negative electrode active material: dispersant: binder is 1:18-90:0.3-4:0.4-5; preferably 1:30-60:0.5-2:0.5-2; Optionally, the negative electrode active material is selected from one or more of carbon-based active particles and silicon-based particles; optionally, the carbon-based active particles are selected from one or more of soft carbon, hard carbon, artificial graphite, natural graphite and mesophase carbon microspheres; the silicon-based particles are selected from pure silicon nanomaterials, silicon-carbon composite materials and SiO x / C composite material, one or more of which 0.3 <x<1.6; The dispersant is selected from one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose, sodium alginate, polyvinyl alcohol, chitosan and β-cyclodextrin; The binder is selected from one or more of styrene butadiene copolymer, polyacrylic acid, sodium polyacrylate, polyimide, polyvinylidene fluoride, nitrile rubber, butadiene rubber, xanthan gum and gum arabic.
12. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, the negative electrode sheet as claimed in claim 10 or 11, a battery separator and an electrolyte.
Citation Information
Patent Citations
Composite conductive agent for lithium ion battery, composite conductive liquid for lithium ion battery, preparation method of conductive agent and conductive liquid and lithium ion battery
CN106099115A
Composite conductive agent of lithium ion battery and preparation method of composite conductive agent
CN106887591A
Conductive agent for negative electrode of lithium ion battery and preparation method for battery containing conductive agent
CN108649207A
Method for preparing high-power lithium-ion battery conductive agent and lithium-ion battery
CN110137499A
Negative electrode composite conductive agent and preparation method thereof, lithium ion battery containing negative electrode composite conductive agent and preparation method of lithium ion battery
CN111916743A